The social resonance of environmental media messages: a connectionist-inspired reception analysis - Pascal Verhoest; Joke Bauwens; Petrus te Braak; Marijke Huysmans (Humanities & Social Sciences Communications)
Abstract This study examines the reasons why certain environmental messages are received negatively by some social groups and not by others. In particular, the study provides insights into the influence of fear appeals in environmental communication and explores how communication strategies can be optimised to encourage environmentally friendly behaviour. In contrast to many studies that adopt a linear perspective on media effects, this study analyses the reception of environmental information as an interaction between media representations and the socially situated cognitive representations of reality stored in recipients’ memories. To operationalise this approach, a method of reception analysis is proposed that combines thought elicitation, semantic coding and multiple correspondence analysis (MCA). This method was used to assess the cognitive resonance of a minimal information condition and three differently framed newspaper-like articles on wastewater reuse in agriculture, which were randomly assigned to four panels with a total of 1040 participants. The results indicate that, independent of framing effects, these articles evoke different interpretations depending on the interplay between the media frames presented and the prior cognitive representations of different groups.